The impact of strategic leadership on improving the organizational health of Yemeni private universities - Shawesh, Zayed Naji; Al-Shakhfir, Abdullah Ahmed (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to determine the impact of strategic leadership on improving the organizational health of Yemeni private universities. The study used the descriptive analytical approach, and the questionnaire was the appropriate tool for collecting information and data. The study community consisted of all academic and administrative leaders of the universities, which were: University of Science and Technology - University of Saba - Andalus University for Science and Technology - Queen Arwa University - University of Modern Sciences). The level of practicing strategic leadership behaviors in Yemeni private universities was high, according to the estimates of the study sample, and the level of organizational health in the universities was high. Therefore, there is an impact of the di strategic leadership on improving the organizational health of Yemeni private universities support the process of creativity and innovation among employees.